The Planning of Human Resource Management with Labor Market Needs: A Case Study at SDN 28 Pontianak Utara - Haryanengsi; Asriati, Nuraini (Jurnal Manajemen Pendidikan, 2024)
Background: Effective HRM planning is essential to ensure that educational institutions can meet the competency requirements of teachers in line with current educational advancements and labor market needs. Purpose: This study aims to analyze human resource management (HRM) planning at SD 28 Pontianak Utara in alignment with labor market demands. Design/method/approach: This research employs a qualitative case study approach, with data collected through in-depth interviews, observations, and document analysis. Participants include the school principal, teachers, and other educational staff at SD 28 Pontianak Utara. Results: The findings reveal that HRM planning at the school requires improvement, particularly in the development of teacher competencies and curriculum adjustments to meet future labor market demands. A gap was identified between the skills taught at the school and those required by the labor market, particularly in technology and 21st-century skills. Contribution/value: This school needs to conduct a comprehensive evaluation of its HRM planning to enhance the relevance of education to the workforce. Recommendations include providing regular training for teachers and updating the curriculum to align with the evolving demands of the labor market.